Plant salinity stress, sensing, and its mitigation through WRKY - Rai, Gyanendra Kumar; Mishra, Sonal; Chouhan, Rekha; Mushtaq, Muntazir; Chowdhary, Aksar Ali; Rai, Pradeep K.; Kumar, Ranjeet Ranjan; Kumar, Pradeep; Perez-Alfocea, Francisco; Colla, Giuseppe; Cardarelli, Mariateresa; Srivastava, Vikas; et al. (Frontiers in Plant Science, 2023)
Salinity or salt stress has deleterious effects on plant growth and development. It imposes osmotic, ionic and secondary stresses,including oxidative stress on the plants and is responsible for the reduction of overall crop productivity and therefore challenges global food security. Plants respond to salinity, by trigerring homoeostatic mechanisms that counter salt-triggered disturbances in the physiology and biochemistry of plants. This involves the activation of many signaling components Codice campo modificato ha eliminato: The salinity (or salt)